PENEGAKAN HUKUMAN MATI DALAM TINDAK PIDANA NARKOTIKA - Salundik (Jurnal Ilmu Hukum Tambun Bungai, 2016)
Enforcement of the death penalty in narcotic crime is causing the pros and cons. Each group, both of which oppose (abolitionist groups) as well as supporting the death penalty (retentionist group), basing his opinion on a strong argument. Of the various arguments advanced abolitionist and retentionist group, can be taken policy synthesis death penalty for drug crimes in Indonesia. n case of emergency drugs such as now, when the drug-related crime has undermined young people and depriving many human lives in Indonesia, is unjust death sentence of one individual drug crimes. So, the main consideration is the sense of justice in society. The death penalty is also applied to give a stern warning to potential drug criminals that we will not compromise with serious crime and it's incredible. But the death penalty is only imposed on the shape of the most evil of drug crimes, such as producing and drug dealers.